Potassium channels in depression: emerging roles and potential targets - Jiahao Zhang; Yao Zhu; Meng Zhang; Jinglan Yan; Yuanjia Zheng; Lin Yao; Ziwei Li; Zihan Shao; Yongjun Chen (Cell & Bioscience)
Abstract Potassium ion channels play a fundamental role in regulating cell membrane repolarization, modulating the frequency and shape of action potentials, and maintaining the resting membrane potential. A growing number of studies have indicated that dysfunction in potassium channels associates with the pathogenesis and treatment of depression. However, the involvement of potassium channels in the onset and treatment of depression has not been thoroughly summarized. In this review, we performed a comprehensive analysis of the association between multiple potassium channels and their roles in depression, and compiles the SNP loci of potassium channels associated with depression, as well as antidepressant drugs that target these channels. We discussed the pivotal role of potassium channels in the treatment of depression, provide valuable insights into new therapeutic targets for antidepressant treatment and critical clues to future drug discovery.